2017
DOI: 10.1371/journal.pone.0172771
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in skeletal muscle microvascular response to exercise as detected by contrast-enhanced ultrasound (CEUS)

Abstract: BackgroundAging involves reductions in exercise total limb blood flow and exercise capacity. We hypothesized that this may involve early age-related impairments of skeletal muscle microvascular responsiveness as previously reported for insulin but not for exercise stimuli in humans.MethodsUsing an isometric exercise model, we studied the effect of age on contrast-enhanced ultrasound (CEUS) parameters, i.e. microvascular blood volume (MBV), flow velocity (MFV) and blood flow (MBF) calculated from replenishment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 64 publications
3
27
1
1
Order By: Relevance
“…Although there is compelling evidence from respirometry conducted in permeabilized human muscle fibers that mitochondrial function intrinsically declines with age (Short et al, 2005; Mellem et al, 2017), we cannot exclude the possibility that changes in muscle perfusion also play an important role in the age-associated decline of mitochondrial function and ultimately whole-body aerobic capacity. For example, it has been suggested that age (Lawrenson et al, 2004; Hearon and Dinenno, 2016; Hildebrandt et al, 2017) and disease (Gueugneau et al, 2016; Wagenmakers et al, 2016; Creager, 2018) may impair the transport of oxygen and nutrients because of a reduction in cardiac function or impairment of peripheral vascular adaptation. Indeed, a wealth of data suggest that both capillary density (Urbieta-Caceres et al, 2012; Barnouin et al, 2017) and vasodilation that occurs under metabolic demand substantially decrease in older adults (Mueller et al, 2017; Tonson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is compelling evidence from respirometry conducted in permeabilized human muscle fibers that mitochondrial function intrinsically declines with age (Short et al, 2005; Mellem et al, 2017), we cannot exclude the possibility that changes in muscle perfusion also play an important role in the age-associated decline of mitochondrial function and ultimately whole-body aerobic capacity. For example, it has been suggested that age (Lawrenson et al, 2004; Hearon and Dinenno, 2016; Hildebrandt et al, 2017) and disease (Gueugneau et al, 2016; Wagenmakers et al, 2016; Creager, 2018) may impair the transport of oxygen and nutrients because of a reduction in cardiac function or impairment of peripheral vascular adaptation. Indeed, a wealth of data suggest that both capillary density (Urbieta-Caceres et al, 2012; Barnouin et al, 2017) and vasodilation that occurs under metabolic demand substantially decrease in older adults (Mueller et al, 2017; Tonson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Contrast‐enhanced ultrasound (CEUS) allows for a dynamic quantification of perfusion in muscle tissue. Being closely linked to the responsiveness and recruitment of muscle fibers and the muscle metabolism, CEUS has been suggested as functional real‐time biomarker for muscle vitality and function beyond morphologic aspects . Originally implemented for assistive diagnostics of liver and kidney tumors in 2004, CEUS has nowadays been translated into the clinical routine of numerous pathologies and was lately evaluated for various musculoskeletal indications, including shoulder pathologies .…”
mentioning
confidence: 99%
“…A new promising tool is the contrast-enhanced ultrasound (CEUS) method that provides a relatively non-invasive imaging technique for clinical and research application [29]. By using this technique, impaired micro-vascular reaction to isometric exercise and attenuated, delayed post-exercise hyperemia were found in middle-aged subjects in comparison to young people without significant differences in vascular morphology and total leg perfusion [30].…”
Section: Aging-related Changes In the Microcirculationmentioning
confidence: 99%